Capsaicin delivery into the skin with lipidic nanoparticles for the treatment of psoriasis. (February 2015) - Agrawal, Udita; Gupta, Madhu; Vyas, S. P.
Abstract The study aims to explore the potential of solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) in improving the topical delivery of capsaicin (CAP) by in vitro and in vivo studies. The lipidic nanoparticles were prepared by solvent diffusion method and were characterized for average particle size, zeta potential and entrapment efficiency. TEM photomicrographs revealed that the particles were nanometric in size. Higher amount of CAP can be encapsulated in the NLCs (87.4 ± 3.28) as compared with SLNs (79.7 ± 2.93%). The cumulative amounts of CAP permeated through the skin and retained in the SC were higher in the case of NLCs as compared with plain drug solution and SLNs. SLNs and NLCs exhibited minimum to no irritation. All the results concluded that NLCs and SLNs have shown a good ability to increase drug accumulation in the various skin layers but NLCs may be a more potential carrier for topical delivery of CAP for an effective therapy of psoriasis.